ANALISIS KESULITAN SISWA DALAM PEMECAHAN MASALAH MATEMATIK SISWA SMA PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINIER - Dewi, Dara Kartika; Ernawati, Ernawati; Nurhayati, Leni; Agina, Selvia; Sarah Khodijah, Siti; Hidayat, Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
The research has a purpose to analyze students' difficulties in solving equation of problem solving ability on linear equations and linear inequalities material. This type of research is a qualitative research with a qualitative descriptive approach. The research subjects were 24 students of class X MA Al - Mubarok. The selection of subjects based on consideration, that is the advice of teacher. Data collection techniques used in this research are the documentation method in the form of student test results with the subject of equations and linear inequalities. Based on the results of research and discussion, the level of problem solving ability of students in the low category, especially in the indicator of re-examining the results of solving the problem. This can be caused by the students' mathematical problem solving ability is still low